Structural and optical studies on Nd doped ZnO thin films. (January 2015) - Deepa Rani, T.; Tamilarasan, K.; Elangovan, E.; Leela, S.; Ramamurthi, K.; Thangaraj, K.; Himcinschi, C.; Trenkmann, I.; SchuIze, S.; Hietschold, M.; Liebig, A.; Salvan, G.; et al.
Highlights: Grain size of the Nd doped ZnO layers varies from 50 nm to 76 nm by SEM. From Raman, the LO phonon is slightly red-shifted and broadened. Presence of crystalline defects in the ZnO lattice confirmed was by Raman studies. A red shift was also observed for Nd doping of ZnO thin films confirmed by PL. Abstract: Thin films of Zn1− x Nd x O were deposited by spray pyrolysis on Si(111) substrates preheated at 400 °C temperature and were studied as a function of neodymium (Nd)-doping concentration. X-ray diffraction (XRD) patterns confirmed that the deposited films possess hexagonal wurtzite ZnO structure. Further, it is observed that the doped films show a preferential orientation along the c -axis (0 0 2), which is perpendicular to the substrate. The un-doped films seem to be having a bit low-crystallinity, which is corroborated by the scanning electron microscope (SEM) analysis that showed nano-crystalline like features. Further, SEM analysis showed that the Nd doping triggers the formation bubble-like structure on top of the nano-crystalline structure. The SEM microstructures are interpreted with the Micro-Raman studies. Photoluminescence (PL) and XRD characterizations indicate that above 5 at.% doping concentrations, the Nd atoms preferentially agglomerate in the large islands.